Evaluasi Faktor Motivasi Pemberian Penyuluhan Kesehatan Oleh Petugas Gizi Di Pos Pelayanan Terpadu Lanjut Usia (Studi Di Puskesmas Kota Banjarbaru Tahun 2016) - Ari Widyarni (Jurnal Kesehatan Indonesia, 2016)
Indonesian Government Regulation No. 43 of 2004, Article 8 states that governments, communities and families are responsible for the realization of efforts to improve the social welfare of the elderly (Elderly). Data Elderly health care coverage in the City Banjarbaru seen still lower than the target of 70% is only 31.2% elderly who receive health care of elderly in the total Banjarbaru City. This research is a quantitative study with a cross-sectional approach. Population and sample are all officers of nutrition in health centers Banjarbaru City totaling 38 people. Data collection was studies using a structured questionnaire on nutritional health center personnel. Bivariate analysis using Pearson Product Moment and Spearman Rank. The results showed that most respondents educated DIII Nutrition, has a period of work over 12 months, working as a nutritionist and aged between 24 years to 48 years. Respondents stated low motivation, stated the job itself was bad and stated the average of policy and administrative, and stated factors related to the motivation of nutritionist is the work itself and policy and administration. It is recommended for the DKK and Public Health to improve coaching and training through regular briefings, seminars and education, improving cooperation and mobilization and increase the motivation to reward achievement in the delivery of nutrition workers in the health education Posyandu Lansia in Banjarbaru City. Keywords : Motivation Factor, Health Counseling, Intergrated Health Services